2005
DOI: 10.1007/s10453-005-9002-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of airborne conidia of Stemphylium vesicarium, the causal agent of brown spot disease of pears, in relation to weather conditions

Abstract: Seven-day volumetric spore samplers were installed in pear orchards of northern Italy, in the years between 1993 and 2002, and operated continuously during the development of brown spot epidemics (mid-April-mid-August), caused by Stemphylium vesicarium. Aerial concentration of conidia was recorded at 2 h intervals to study their diurnal and seasonal patterns and the influence of weather conditions. The diurnal periodicity of aerial conidia showed a peak around midday and low counts in the dark. The increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 45 publications
4
21
0
1
Order By: Relevance
“…Desse modo, o entendimento dos fatores que influenciam no desenvolvimento das doenças é essencial para tomada de decisões para o manejo adequado. ROSSI et al (2005) verificaram que o aumento da concentração de esporos de Stemphylium vesicarium em área com cultura de pêra foi correlacionado com umidade relativa do ar, período de molhamento foliar no início da manhã e com o aumento do vento no final da manhã e à tarde. Segundo STEPALSKA & WOLEK (2005), trabalhos realizados na Polônia indicaram que a temperatura é a variável mais influente na concentração aérea de esporos de Alternaria, Botrytis e Cladosporium, com correlações significativas e positivas.…”
Section: IIunclassified
“…Desse modo, o entendimento dos fatores que influenciam no desenvolvimento das doenças é essencial para tomada de decisões para o manejo adequado. ROSSI et al (2005) verificaram que o aumento da concentração de esporos de Stemphylium vesicarium em área com cultura de pêra foi correlacionado com umidade relativa do ar, período de molhamento foliar no início da manhã e com o aumento do vento no final da manhã e à tarde. Segundo STEPALSKA & WOLEK (2005), trabalhos realizados na Polônia indicaram que a temperatura é a variável mais influente na concentração aérea de esporos de Alternaria, Botrytis e Cladosporium, com correlações significativas e positivas.…”
Section: IIunclassified
“…Ascospores are found on fallen pear leaves on orchard floors only during early spring, but epidemics usually start in summer (Llorente and Montesinos 2006). Since only airborne conidia are detected in spore traps during summer (Rossi et al 2005a), conidia may be the prevalent primary inoculum of the disease. Conidia are rarely observed in lesions on affected pear leaves during summer.…”
Section: Introductionmentioning
confidence: 99%
“…1d-f) even though weather conditions were less favourable for sporulation. In July-September, RH, rainfall and number of rainy days were lower in 2004 than in the other 2 years (Table 3); the number of days with favourable conditions for sporulation estimated according to Rossi et al (2005bRossi et al ( ) were 12, 23 and 26 in 2003Rossi et al ( , 2004Rossi et al ( and 2005 Pathogenicity of S. vesicarium strains Forty strains of S. vesicarium were obtained from the spore traps in 2006: 11 from type I inoculum source, 19 from II, 6 from III and 4 from IV; no strains were obtained from the uninoculated plots (V). All these strains caused brown spot symptoms on the inoculated leaves of cv.…”
Section: Seasonality In Conidial Trappingmentioning
confidence: 99%
“…Ascospores are released from February to May or early June (Llorente et al 2003), but disease symptoms usually first appear from mid-June (Ponti et al 1982), when few or no ascospores are present in the orchard air (Picco et al 1996). In this period, conidia are usually abundant and continue to be airborne during the pear-growing season (Rossi et al 2005b), though sporulation rarely occurs on infected pear tissues (Maccaferri et al 2003). Recent studies (Rossi et al 2005a) demonstrated that S. vesicarium strains are able to colonize dead tissues of herb plants as saprophytes and to produce abundant ascospores and conidia that are capable of infecting pear.…”
Section: Introductionmentioning
confidence: 98%